2022
DOI: 10.1097/ta.0000000000003804
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of 30-day readmissions after emergency general surgery procedures: Are risk factors modifiable?

Abstract: Factors related to EGS 30-d readmissions are mostly unmodifiable. However, rigorous CQI, implementation of standardized intra and postoperative measures (ERAS) and a post-discharge surveillance system may decrease EGS readmissions. #EGS #EGSquality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Recent evidence proposes that unmodifiable patient and disease-related factors may drive hospital readmissions in emergency general surgery. 39 Hence, it was suggested that readmissions might be reduced by implementing postdischarge surveillance systems leveraging telehealth and in-person outpatient care provided by surgeons, primary care providers, and appropriate specialists. These postdischarge interventions will require data collection and analytic mechanisms for episodes of care that can document and collapse information over many months to years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence proposes that unmodifiable patient and disease-related factors may drive hospital readmissions in emergency general surgery. 39 Hence, it was suggested that readmissions might be reduced by implementing postdischarge surveillance systems leveraging telehealth and in-person outpatient care provided by surgeons, primary care providers, and appropriate specialists. These postdischarge interventions will require data collection and analytic mechanisms for episodes of care that can document and collapse information over many months to years.…”
Section: Discussionmentioning
confidence: 99%
“…The readmission rate in our study was 15.1% for the aggregate cohort, and we found a substantial number of patients who required additional operations or interventions. Recent evidence proposes that unmodifiable patient and disease-related factors may drive hospital readmissions in emergency general surgery 39 . Hence, it was suggested that readmissions might be reduced by implementing postdischarge surveillance systems leveraging telehealth and in-person outpatient care provided by surgeons, primary care providers, and appropriate specialists.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with recent literature, most factors related to readmission in this study are non-modifiable (ASA score, stomal placement etc.). Still, when zooming in on the specific mechanism behind each readmission, we find that they often are multifactorial and in several instances, preventable [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%